Novel antifungal activity of Q-Griffithsin, a broad-spectrum antiviral lectin. Issue 12 (17th December 2021) - Nabeta, Henry; Kouokam, Joseph C; Lasnik, Amanda; Fuqua, Joshua; Palmer, Kenneth E
Abstract : Background: There is a rising global trend in candida strains with high resistance to fluconazole and other antifungal drugs, hence the need for novel agents. Here, we investigated the anti-Candida activity of Q-Griffithsin (Q-GRFT), a lectin naturally produced by the red-sea algae, Griffithsia spp. Methods: To assess in vitro growth inhibitory activity, C. albicans was incubated with Q-GRFT on agar plates and in broth media. We investigated GFP-bound Q-GRFT's ability to adhere to C. albicans using fluorescence microscopy and fluorescence intensity assessments. To demonstrate in vivogrowth inhibitory activity, CBA/J mice were treated per vaginam with Q-GRFT followed by challenge with C. albicans, and fungal burden determined following vaginal lavage. Results: Wild type fluorescently labeled Q-GRFT displayed higher fluorescence than the lectin-binding site deficient variant following incubation with C. albicans . Q-GRFT localized around the fungal cells and bound to α-mannan in the cell wall. Q-GRFT significantly inhibited C. albicans growth in broth and on agar plates, disrupted the integrity of the cell wall, and induced ROS formation. The lectin significantly inhibited the growth of C. glabrata, C. parapsilosis and C. krusei, with modest activity against C . auris CDC388 and C. auris CDC389 strains in vitro. Topical treatment resulted in a lower fungal burden compared to the vehicle control group in vaginal candidiasis. Conclusion: Q-GRFT binds to and inhibits C. albicans growth both in vitro and in vivo. Further studies are needed to establish the mechanism of growth inhibition.